Is Neurodevelopmental Assessment in Early Childhood Predictive of Performance Assessed Later in Childhood and Adolescence in Sub-Saharan Africa? A Systematic Review of the Literature - (:unkn) unknown (My University, 2024)
Background - Most neurodevelopmental tests used to assess child development in sub-Saharan Africa were developed in western or high-income countries, raising the question of their usefulness with African children.Objective - This systematic review identified and synthesized key findings from studies measuring development in children in Sub-Saharan Africa in early childhood and again at school age, to assess neurocognitive associations longitudinally from infancy through middle childhood.Methods - The study was based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses method, selecting articles referenced in the PubMed, PsycInfo, and Embase databases using the following inclusion criteria: published between 2000 and 2022, written in French or English, and presenting results dealing with the objective assessment of child’s neurodevelopment. All articles were registered in the Zotero reference manager and analyzed by title, abstract, and full text. Results - Several of the seven selected studies confirmed that attention and working memory in infancy can predict children’s neurocognitive performance, including mathematical ability, at school age. In two of the studies, children with poor mental development at 1 year of age are more likely to present with poorer behavioral development at school age, including learning difficulties in school and risk for grade repetition.Conclusion - Cognitive ability assessed in early childhood is strongly associated with performance at school age in cohorts of African children followed longitudinally. Even with assessments adapted cross-culturally, infants and preschoolers at risk for poor developmental outcomes can be identified to better receive strategic early interventions to enhance their development.
Keywords: African Research